Comparison of effectiveness between Haloperidol and Quetiapine in acute manic episode - Khan, Noman; Usama Bin Zubair; Saad Ali Khan; Junaid Ul Islam; Syed Azhar Ali Kazmi; Abrar Khan (Journal of the Pakistan Medical Association, 2022)
This study was conducted to compare the response rate of Quetiapine and Haloperidol in patients with acute manic episodes. A total of 120 patients with acute episode of mania with baseline Young Mania Rating Scale (YMRS) of more than 20 were included and randomly allocated to either Quetiapine (Group A) or Haloperidol (Group B). Each patient was assessed at baseline. YMRS was administered at the start and at follow-up visit after six weeks. Comparison of response rate (>50% reduction in YMRS) was not statistically significant between the two groups (70% vs. 71.7%; p=0.410) after six weeks in acute manic episode. Quetiapine and Haloperidol emerged as equally effective pharmacological strategies for the treatment of bipolar mania. Quetiapine may be used as an alternative to conventional antipsychotics; Haloperidol can be used as replacement of Quetiapine as well, as it is of low cost. Key Words: Acute manic episode; Quetiapine; Haloperidol